Preparation and characterization of nanocomposites based on COOH functionalized multi-walled carbon nanotubes and on poly(trimethylene terephthalate) (eXPRESS Polymer Letters)
Poly(trimethylene terephthalate) nanocomposites containing COOH functionalized multi-walled nanotubes were synthesized with in situ polymerization method. The microstructure of the nanocomposites was studied by SEM, in terms of the dispersion state of the nanotubes and the polymer–nanotube interface. The thermal behaviour, mechanical properties and conductivity of these resultant PTT/MWCNTs nanocomposites were studied. The effect of the presence of MWCNTs on cold crystallization of PTT was monitored by dielectric spectroscopy. From thermal analysis study, it is found that the melting temperature and glass transition temperature are not significantly affected by the addition of MWCNTs. The crystallization temperature of PTT matrix is affected by the presence of CNTs. Nanocomposites have slightly higher degree of crystallinity than neat PTT and their thermo-oxidative stability is not significantly affected by the addition of MWCNTs. The study of the isothermal cold crystallization of amorphous PTT and its nanocomposites monitored by dielectric spectroscopy reveals that the presence of MWCNTs have influence on crystallization rate, especially at higher concentration (0.3 wt%). In comparison with neat PTT, the MWCNTs reinforced nanocomposites posses higher tensile strength and Young’s modulus at low MWCNTs loading (0.05–0.3 wt%). In addition, all nanocomposites show reduction of brittleness as compared to the neat PTT. The electrical percolation threshold was found between 0.3 and 0.4 wt% loading of MWCNTs.